Grain intermodal terminals: evaluation of pure technical efficiency by Data Envelopment Analysis - Maria Gabriela Mendonça Peixoto; Maria Cristina Angélico Mendonça; Marcel Andreotti Musetti; Mario Otavio Batalha; Renato Luiz Sproesser (Production)
Abstract This paper aimed to verify if terminals with productive efficiency also have pure technical efficiency, using DEA (Data Envelopment Analysis) technique. The research approach was the qualitative-quantitative or mixed, with exploratory purpose; the research method defined was the case study (multicases); data were collected through interviews using a structured questionnaire and non-probability for convenience sampling. While the application of Charnes, Cooper and Rhodes (CCR) model observed that only three (4, 7 and 11), of the twelve analyzed Decision Making Units (DMUs) have total technical efficiency, through Banker, Charnes and Cooper (BCC) model, it was possible to observe that these terminals were the only ones with pure technical efficiency. The three inefficient DMUs (1, 2 and 12) showed pure technical efficiency, suggesting that these terminals might present probable scale operations’ inefficiency, aspect not addressed in this paper.